Using Competency Mapping to Improve Online Education - Katherine Adler; Sue McDaniel; David A Line (Academic Chairpersons Conference Proceedings, 2018)
The growth of online education has coincided with the resurgence in Competency Based Education (CBE). This trend has introduced new opportunities to assess student progress and program outcomes. This interactive session explores ways of getting the most out of CBE in the online world.
Keywords: mapping; improving students; competency based education